Adaptation of social utopia in post-modern society - Dmitrievich Leontyev, Gleb (2021)
System-forming invariants of utopia are analyzed – rationality, criticality, transcendentality, universalism, and projectivity – in the context of post-modern world outlook. The agenda of utopian consciousness is actualized through the statements about the anti-utopian character of post-modernism and the idea of “the end of utopia”, concordant with “the end of history”. The research objective is to prove the prolongation of utopian discourse after the period of modernism on the basis of systemic approach and philosophical conceptions substantiating the qualitative specificity of the modern society. The analysis is based on the correlation between the presence of specific features of utopian consciousness in the world-outlook picture of the world and the viability of the social utopia phenomenon. Each of the system-forming characteristics of utopia is revealed in the contradictory context of post-modernism. The classical type rationality invariant is manifested through optimization of the social organization pattern, which plays an instrumental role in relation to the moral ideal. In the epoch after modernism, it is “reasonable organization” that represents the utopian ideal. The criticality invariant: on the one hand, post-modernism takes a time-serving position of “linguistic escapism”. On the other hand, it criticizes the style of reasoning of the previous epoch. Criticality and pluralism testify to the ability for alternative view at the things existent, the said view being based on the social ideal. The projectivity invariant: on the one hand, post-modernism marks “the end of history” and time. On the other hand, the gnoseological plurality of post-modernism implies individual, polysemantic vision of the objective reality, facilitating the formation of multiple utopian projects, tolerate to simultaneous existence. The transcendentality invariant: on the one hand, post-modernism excluded transcendental narratives from its semantic field. On the other hand, hyperreality with its simulacras generates belief in new metaphysical meanings. The universality invariant: on the one hand, social construction after modernism does not pretend to absolute truth and universal happiness. On the other hand, the global issues actualize the universality approach, while tolerate post-modernism does not deny the co-existence of individualistic utopias and megaprojects common to all mankind. As a result, the authors make a conclusion that the classical utopia crisis has been overcome and there is a trend for further development of utopian discourse due to adaptive transformation of utopian invariants in the society after modernism.